Systematic Review: Outcomes by Duration of NPO Status prior to Colonoscopy. (16th July 2017) - Shaukat, Aasma; Malhotra, Ashish; Greer, Nancy; MacDonald, Roderick; Wels, Joseph; Wilt, Timothy J.
Abstract : Background/Aims . Variation exists among anesthesia providers as to acceptable timing of NPO ("nothing by mouth") for elective colonoscopy procedures. There is a need to balance optimal colonic preparation, patient convenience, and scheduling efficiency with anesthesia safety concerns. We reviewed the evidence for the relationship between NPO timing and aspiration incidence and colonoscopy rescheduling. Methods . We searched MEDLINE (1990–April 2015) for English language studies of any design and included them if at least one bowel preparation regimen was completed within 8 hours of colonoscopy. Study characteristics, patient characteristics, and outcomes were abstracted and verified by investigators. We determined risk of bias for each study and overall strength of evidence for primary and secondary outcomes. Results . We included 28 randomized controlled trials (RCTs), 2 controlled clinical trials, and 10 observational reports. Six studies reported on aspiration; none found that shorter NPO status prior to colonoscopy increased aspiration risk, though studies were not designed to assess this outcome (low strength of evidence). One RCT found fewer rescheduled procedures following split-dose preparation but NPO status was not well-documented (insufficient evidence). Conclusions . Aspiration incidence requiring hospitalization during colonoscopy with moderate or deep sedation is very low. No study found that shorter NPO status prior to colonoscopy increased aspiration risk. We did not find direct evidence of the effect of NPO status on colonoscopy rescheduling.